Model Persediaan dengan Permintaan Bergantung pada Harga Jual dan Tingkat Persediaan dengan Faktor Deteriorasi - Widyoretno Adiani; Dharma Lesmono; Taufik Limansyah (Jurnal Ilmiah Teknik Industri, 2019)
Inventory management and control are needed, especially for retailers, to make their business run smoothly. Inventory management is related to the purchase, storage, and sale of goods. Therefore, the determination of the right amount of inventory in hands is crucial in this situation. Low inventory levels will cause a higher probability of shortage, but on the other hand, having a lot of inventory in hands will incur higher holding costs, extra storage space, and deterioration of goods in hands. In this paper, we propose an inventory model with the inventory and price-dependent demand. We also consider a deterioration factor in our model. There are two models developed in this paper, namely the linear deterioration rate model with constant holding cost and the model of the deterioration rate with Weibull distribution with linear time-dependent holding cost. The purpose of the model is to find the optimal price and ending inventory level that maximizes the average profit. Sensitivity analysis is also performed to find the effect of parameter changes in our model to the optimum solution. We found that model with Weibull deterioration rate and linear holding costs will give a higher average profit.